DEVELOPMENT TRENDS OF LOCAL COUNCILS IN THE AUTONOMOUS REGIONS OF THE NORTH CAUCASUS TERRITORY DURING THE NEW ECONOMIC POLICY (1924–1929) - Kokorhoeva, Dugurhan Sultangireevna (History, Archeology and Ethnography of the Caucasus, 2025)
This article examines the development trends of local councils within the complex and multi-ethnic autonomous societies of the North Caucasus Territory between 1924 and 1929. This period is particularly relevant for understanding the interactions between state authority and the populace, as well as the strengthening of the state apparatus. While crucial, the formation and consolidation of local councils in the North Caucasus autonomies during the New Economic Policy (NEP) era remain underexplored. Therefore, this study clarifies these development trends. Methodologically, the research employs principles of systemicity and historicism, alongside diachronic and synchronous comparative analysis. Findings indicate that the transition from appointed revolutionary committees to elected councils in the North Caucasus autonomies occurred gradually, spanning from 1921 to 1924, with faster implementation in North Ossetia and Adygea compared to Chechnya. By the mid-1920s, aul and district councils suffered from organizational and personnel weaknesses. Specifically, chairpersons and secretaries of village councils often comprised individuals deemed undesirable by the Communist Party, including former tsarist officials, clergy, and disloyal intelligentsia. Furthermore, record-keeping in Russian presented a barrier to understanding for the local population. Rural gatherings frequently supplanted aul unions, with decisions often influenced by wealthy segments of society, leading to a de facto “dual power” dynamic at the local administrative level. The “revival of the Soviets” policy (1924–1929) in the North Caucasus autonomies aimed to address these issues by focusing on the organizational and financial strengthening of councils, translating documents into regional languages, eradicating illiteracy among deputies, and ensuring a politically loyal core of council employees drawn from farm laborers and impoverished workers. This policy also sought to eliminate the political influence of rural gatherings and affluent social strata. Ultimately, the transition from the NEP to collectivization fundamentally altered the functions of local councils, prioritizing the management of economic modernization.